Utility of bats (Chiroptera) as ecological indicators in Peninsular Malaysia / Khairunnisa binti Syaripuddin - Syaripuddin, Khairunnisa (2014)
As ecologists we are tasked with studying the effects of environmental changes on ecosystems, but it is impossible to study every species and every interaction. Therefore, a relatively small group of species must be chosen as a proxy for monitoring general patterns of ecological change. Bats might be suitable for the role as ecological indicators because they have high species richness and abundance, represent several distinct feeding guilds, occupy high trophic positions, and perform key ecosystem services such as pollination, seed dispersal, nutrient recycling and arthropod control. A critical prerequisite for an ecological indicator group is stable and accurate species recognition. In this regard, the first study was conducted on the changing perspectives of diversity of bats at Ulu Gombak, particularly looking at the role of DNA barcoding in species recognition. During the surveys, DNA barcodes were obtained from 45 bats which were assigned to seven species. Five of these were dark taxa, previously reported species which lack formal description. One bat belonged to a putative cryptic species which had not been reported previously. These five species were added to the cumulative checklist for Ulu Gombak taking the total to 57 species of bats. The high number of cryptic species uncovered supports the prediction that the number of bat species in Ulu Gombak is significantly underestimated. However, the findings showed that DNA barcoding can be employed easily and effectively to recognize well-characterized and stable species units within and across surveys. The second study assessed the potential of bats as biodiversity indicators, i.e. bat diversity as a proxy measure for total biodiversity. For this study, four key criteria and a comparison with beetles and butterflies were used. Based on the four key criteria, bats and butterflies showed good potential as bioindicators and should be given more prominence in the evaluation of biodiversity in Southeast Asia. The third study assessed bats as indicators of environmental contamination with a case study looking at mercury contamination in hydroelectric reservoirs. Significantly higher concentrations of mercury were found in the fur of insectivorous bats than frugivorous bats suggesting mercury was being exported out of the reservoirs by aquatic insect prey. Ten bats (H. cf. larvatus) sampled at Kenyir Lake had mercury concentrations approaching or exceeding 10 mg/kg, which is the threshold at which detrimental effects occur in humans, bats and mice. Future hydroelectric projects should be aware that mercury contamination can occur due to construction of reservoirs and move through the ecosystem through trophic pathways. The combined findings of the three studies suggest that bats can be effectively employed as ecological indicators. Therefore, bats are recommended to play a central role in monitoring ecological change in Peninsular Malaysia in the years to come.